Strategi Komunikasi Dinas Pendidikan dalam Gerakan Swasembada Sekolah untuk Meningkatkan Kualitas Pendidikan - Anum, Adelina; Akbar, M. Fikri; Asmaria; Ati, Henny Dewi Laras; Perdana, M. Harviend Gilang (Unitri Press, 2025)
This study explores the communication strategy of the South Lampung Regency Government in implementing the Swasembada Sekolah Movement to enhance educational quality and reduce dropout rates. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, documentation, and questionnaires. The research took place in Sukamarga Village, Sidomulyo District, a pilot area for the program. Findings reveal that the communication strategy was systematically implemented across regency, district, village, and school levels. Key stakeholders included the Department of Education, village heads, school principals, and Swasembada Sekolah Ambassadors. Communication methods encompassed direct channels such as face-to-face meetings, roadshows, and focus group discussions, as well as indirect media like social media, YouTube, and local press. The strategy effectively raised public awareness about the importance of education and increased participation in alternative education programs (Kejar Paket) for dropouts. Notably, South Lampung’s Human Development Index (HDI) surpassed 70 in 2024, indicating positive social impact. However, the study identifies a gap in digital communication, with minimal activity on official websites and social media managed by the Education Department. Therefore, the research recommends optimizing digital platforms, strengthening inter-agency coordination, and enhancing supporting infrastructure and human resources to ensure the movement's long-term sustainability. Abstrak Penelitian ini mengkaji strategi komunikasi dalam implementasi Gerakan Swasembada Sekolah yang digagas oleh Pemerintah Kabupaten Lampung Selatan sebagai upaya meningkatkan kualitas pendidikan dan menurunkan angka putus sekolah. Pendekatan yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data berupa observasi, wawancara mendalam, dokumentasi, dan penyebaran kuesioner. Lokasi penelitian berada di Desa Sukamarga, Kecamatan Sidomulyo, yang menjadi salah satu desa percontohan. Hasil penelitian menunjukkan bahwa strategi komunikasi telah terstruktur dari tingkat kabupaten hingga kecamatan, desa, dan sekolah, melibatkan berbagai pihak seperti Dinas Pendidikan, kepala desa, kepala sekolah, serta Duta Swasembada Sekolah sebagai komunikator utama. Pendekatan komunikasi dilakukan secara langsung (tatap muka, roadshow, FGD) dan tidak langsung (media sosial, YouTube, media massa). Dampak strategi ini terlihat dari meningkatnya kesadaran masyarakat terhadap pentingnya pendidikan dan partisipasi dalam program alternatif seperti Kejar Paket. Indeks Pembangunan Manusia (IPM) Kabupaten Lampung Selatan juga meningkat, melampaui angka 70 pada tahun 2024. Namun, pemanfaatan media digital oleh Dinas Pendidikan masih kurang optimal, ditandai dengan tidak aktifnya situs resmi dan minimnya penggunaan media sosial. Oleh karena itu, penelitian ini merekomendasikan penguatan sistem komunikasi digital, peningkatan koordinasi vertikal, serta perbaikan infrastruktur dan SDM guna menjamin keberlanjutan gerakan ini.